Pengaruh Kepemilikan Saham dan Leverage Terhadap Agresivitas Pajak Perusahaan - Ghaisani Alfira Nugraheni; Alek Murtin (Universitas Muhammadiyah Yogyakarta, 2019)
Many taxpayer in Indonesia did tax aggresiveness, especially corporate taxpayer of 80%. This is proven survey reported by IMF investigator in 2016, that Indonesia ranks 11th out of 30th countries on tax aggressiveness carried out by the company. Tax aggressiveness is an action to minimize tax burden by conducting tax planning which could be legal or illegal. Tax aggressiveness can measured with Effective Tax Rate (ETR). This research aimed to examine the effect of share ownership and leverage toward corporate tax aggressiveness. This population in this study is the listed manufacturing companies in Indonesian Stock Exchange in 2015 until 2017. The sample was determained by the nonprobability sampling method purposive sampling technique, so 33 maufacturing companies have been selected as research sample. Type of data used was secondary data obtained from www.idx.co.id. The method of analysis used is multiple regression analysis by using SPSS version 15.0. The result of research show that institutional ownership and public ownership have negative significant effect toward corporate tax aggressiveness. Managerial ownership and leverage have no effect toward corporate tax aggressiveness. Adjusted R Square value of institutional ownership, managerial ownership, public ownership, and leverage toward tax aggressiveness is 7,4%.